2016
DOI: 10.1371/journal.pone.0167416
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preconception Micronutrient Supplementation on Anemia and Iron Status during Pregnancy and Postpartum: A Randomized Controlled Trial in Rural Vietnam

Abstract: ObjectivePreconception micronutrient interventions may be a promising approach to reduce anemia and iron deficiency during pregnancy, but currently we have limited data to inform policies. We evaluated whether providing additional pre-pregnancy weekly iron-folic acid (IFA) or multiple micronutrient (MM) supplements compared to only folic acid (FA) improves iron status and anemia during pregnancy and early postpartum.MethodsWe conducted a double blind randomized controlled trial in which 5011 Vietnamese women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 42 publications
2
46
1
5
Order By: Relevance
“…In the case of iron and zinc, supplementation increased the intake above the recommended level. In the studies of de Sá et al and Nguyen et al, which considered iron supplementation during pregnancy, similar results were found [ 34 , 35 ]. These authors, however, noted that despite the increase in the intake of iron by supplementation, the hoped-for reduction in the occurrence of anaemia among women was not achieved.…”
Section: Discussionsupporting
confidence: 69%
“…In the case of iron and zinc, supplementation increased the intake above the recommended level. In the studies of de Sá et al and Nguyen et al, which considered iron supplementation during pregnancy, similar results were found [ 34 , 35 ]. These authors, however, noted that despite the increase in the intake of iron by supplementation, the hoped-for reduction in the occurrence of anaemia among women was not achieved.…”
Section: Discussionsupporting
confidence: 69%
“…<11 gm/dl), while 14 women had SFC<15 ng/ml, for a frequency of anemia, ID and IDA of 19.3%, 15.9% and 11.4%. These figures coincided with that previously reported by Sukrat et al (2) and Siridamrongvattana et al (3) and with the recently reported by Nguyen et al (25) who found 20% of pregnant women were anemic, 14% had low iron stores and 3% had IDA and by Okafor et al (26) who detected ID and IDA in 20% and 17.9% of pregnant women.…”
Section: Discussion:-supporting
confidence: 92%
“…Women were then followed up prospectively to identify pregnancies ( n = 1,813) and evaluate birth outcomes ( n = 1,579). Results from the original trial show that weekly supplementation with MM or IFA before conception did not affect birth outcomes compared with FA (Ramakrishnan et al, ), but resulted in modest increases in maternal and infant iron stores (Nguyen, Young, et al, ) and improved maternal mental health among women at risk for depression (Ramakrishnan et al, ). In the second phase, all live singleton births were followed up for growth at 1 year and child development at 2 years of age ( n = 1,458), the sample used in the current analyses.…”
Section: Methodsmentioning
confidence: 99%